Single-Walled Carbon Nanotubes Attenuate Cytotoxic and Oxidative Stress Response of Pb in Human Lung Epithelial (A549) Cells - Ahamed, Maqusood (Int J Environ Res Public Health, 2020)
Combined exposure of single-walled carbon nanotubes (SWCNTs) and trace metal lead (Pb) in ambient air is unavoidable. Most of the previous studies on the toxicity of SWCNTs and Pb have been conducted individually. There is a scarcity of information on the combined toxicity of SWCNTs and Pb in human cells. This work was designed to explore the combined effects of SWCNTs and Pb in human lung epithelial (A549) cells. SWCNTs were prepared through the plasma-enhanced vapor deposition technique. Prepared SWCNTs were characterized by x-ray diffraction, x-ray photoelectron spectroscopy, scanning electron microscopy, and dynamic light scattering. We observed that SWCNTs up to a concentration of 100 µg/mL was safe, while Pb induced dose-dependent (5–100 µg/mL) cytotoxicity in A549 cells. Importantly, cytotoxicity, cell cycle arrest, mitochondrial membrane potential depletion, lipid peroxidation, and induction of caspase-3 and -9 enzymes following Pb exposure (50 µg/mL for 24 h) were efficiently attenuated by the co-exposure of SWCNTs (10 µg/mL for 24 h). Furthermore, generation of Pb-induced pro-oxidants (reactive oxygen species and hydrogen peroxide) and the reduction of antioxidants (antioxidant enzymes and glutathione) were also mitigated by the co-exposure of SWCNTs. Inductively coupled plasma-mass spectrometry results suggest that the adsorption of Pb on the surface of SWCNTs could attenuate the bioavailability and toxicity of Pb in A549 cells. Our data warrant further research on the combined effects of SWCNTs and Pb in animal models.